2013
DOI: 10.3201/1907.130313
|View full text |Cite
|
Sign up to set email alerts
|

Undetected Multidrug-Resistant Tuberculosis Amplified by First-line Therapy in Mixed Infection

Abstract: Infections with >1 Mycobacterium tuberculosis strain(s) are underrecognized. We show, in vitro and in vivo, how first-line treatment conferred a competitive growth advantage to amplify a multidrug-resistant M. tuberculosis strain in a patient with mixed infection. Diagnostic techniques that identify mixed tubercle bacilli populations are needed to curb the spread of multidrug resistance.A s the number of multidrug-resistant tuberculosis (TB) cases continues to rise, so does the amplification of multidrug-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Furthermore, the advent of high resolution tests for genetic variation has revealed that individuals may simultaneously harbor infections with more than one distinct strain of M. tuberculosis (Warren et al, 1999;Sola et al, 2003;Kremer et al, 1999;van Embden et al, 1993;Imaeda, 1985). This phenomenon, which we will refer to as "mixed infection", has been linked with poor treatment outcome when the co-infecting strains differ with respect to drug susceptibility (van Rie et al, 2005;Hingley-Wilson et al, 2013) and is predicted to influence the impact of population-level interventions against tuberculosis (Cohen et al, 2008;Rodrigues et al, 2007;Colijn et al, 2009;Sergeev et al, 2011;Mills et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the advent of high resolution tests for genetic variation has revealed that individuals may simultaneously harbor infections with more than one distinct strain of M. tuberculosis (Warren et al, 1999;Sola et al, 2003;Kremer et al, 1999;van Embden et al, 1993;Imaeda, 1985). This phenomenon, which we will refer to as "mixed infection", has been linked with poor treatment outcome when the co-infecting strains differ with respect to drug susceptibility (van Rie et al, 2005;Hingley-Wilson et al, 2013) and is predicted to influence the impact of population-level interventions against tuberculosis (Cohen et al, 2008;Rodrigues et al, 2007;Colijn et al, 2009;Sergeev et al, 2011;Mills et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence of heteroresistance is unknown and is presumably dependent on the local resistance epidemiology. Findings of heteroresistance are accidental, and simple methods for the detection are needed (6).…”
Section: P Atients With Tuberculosis (Tb) That Harbor Drug-susceptiblementioning
confidence: 99%
“…In addition, it represents an open ended one size fits all approach that could allow the reunification of TB microbiology with other sputum microbiology, particularly as metagenomics has already been shown to work on other respiratory tract pathogens, including bacteria and viruses (Lysholm et al, 2012;Fischer et al, 2014). It also aids in the detection of mixed infections (Chan et al, 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 2013; Koser et al, 2013), which are clinically important, but hard to recognise (Shamputa et al, 2004;Warren et al, 2004;Cohen et al, 2011;Wang et al, 2011;Hingley Wilson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to under recognition of mixed infections, where more than one strain from the M. tuberculosis complex is present or where TB co occurs with infection by other mycobacteria (Shamputa et al, 2004;Warren et al, 2004;Cohen et al, 2011;Wang et al, 2011). This can lead to difficulties in treatment when strains or species susceptible to conventional anti tuberculous treatment co exist with resistant strains or species within the same patient (Hingley Wilson et al, 2013).As an alternative to culture and phenotypic sensitivity testing, the WHO has recently recommended a new, rapid, automated, real time amplification based TB diagnostic test, the Xpert MTB/RIF assay (WHO, 2011). This system allows simultaneous detection of M. tuberculosis and rifampicin resistance mutations in a closed system, suitable for use in a simple laboratory setting, while providing a result in less than two hours directly from sputum samples (Helb et al, 2010).…”
mentioning
confidence: 99%